New insights into the treatment of severe asthma in children. Issue 3 (June 2015) - Giovannini-Chami, Lisa; Albertini, Marc; Scheinmann, Pierre; de Blic, Jacques
Summary: Severe asthma accounts for 0.5% of the general paediatric population and 4.5% of children with asthma, representing the major burden of asthma-health-care-associated costs. After ensuring a diagnosis of asthma and excluding difficult-to-treat patients with co-morbidities and non-adherence profiles, there remains children with real therapy-resistant asthma for whom the recommendations are to treat beyond guidelines. We describe new insights into the treatment of severe asthma in children, regarding both "classic drugs" (corticosteroids, bronchodilators) and innovative biological therapies targeting airway inflammation and impaired innate immunity. All of these new avenues remain to be studied and validated in children and will require fine clinical and biological phenotyping.